Birds of the upv Miagao, Campus, Miagao, Iloilo and some of their feeding habits. - Sartaguda, John Lester Vencer
The study was conducted in an attempt to identify the different species of birds found within the UPV Miag-ao campus. Five sampling sites were taken from the total campus area where the identification and the counting of birds were done using 10x50 Bushell binocular. Identification was then based on Philippine Birds by Du Pont (1971) and the Birds of the Philippines by Gonzales (1977)., Results showed that there were seventeen species found in all of the sampling sites, eleven of which are considered as endemic. All species found were resident or native species and no migrant species were found during the sampling. Of the seventeen species, three species were found to be common on all sampling sites; They are Passer montanus (Maya), Pycnotus goiavier (Ol-ol) and Rhipidura javanica nigritorquis (Maria Kapra). Most of the birds found in the campus were generalist feeders. Fruits of Kamunsil (Pithecolobium dulce) and aratiles (Muntigia calabra) as well as grasses, insects and fishes from the streams and water reservoir of the campus are the main source of food for most of the birds seen during the sampling. Sampling site 5 (Freshwater Aquaculture Station Area) was found to have the most number of species with thirteen and the most number of individual birds sighted per day with 101.14 individuals. Sampling site 4 (Staff Houses-Dormitory Area) was found to have the least number of species with and sampling site 3 (Administration Building-Infirmary Area) has the least number of individual birds sighted per day with 31.56 individuals. The computation for the index of dominance showed that site 4 has the highest index value with 0.407 and site 3 has the lowest value with 0.191. For the Shannon index of general diversity and eveness index, site 3 has the highest indices for both with 0.94 and 0.985 respectively. Sampling site 4 has the lowest value for both respective indices with 0.45 and 0.70. Sites 2 (CF Area) and 5 (FAS area) are the most similar sites with similarity index of 0.43. Index of similarity between sites 4 and 5 has the lowest with 0.22. Sampling site 5 has the highest density with 101.14 individuals sighted per day per an estimated area of one square kilometer. Site 3 has the lowest with 31.56 individuals per day per an estimated area of one square kilometer.